Association Between Androgenetic Alopecia and Dyslipidemia in Male Patients: Evidence From a Hospital-Based Study - Syed Bilal Ahmed, Sajida Jabeen, Asadullah Khan, Neelam Ayub (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Androgenetic alopecia (AGA) is the most common cause of hair loss in men, characterized by progressive miniaturization of scalp hair. Recent evidence suggests that AGA may be associated with metabolic disturbances, including dyslipidemia, which is a well-established cardiovascular risk factor. Objective: To determine the frequency of dyslipidemia in male patients with androgenetic alopecia. Methods: A cross-sectional study was conducted among 130 male patients aged 20–50 years with clinically diagnosed AGA, attending the dermatology department of PGMIQ/ BMC Hospital Quetta, from January 2023 to June 2023. Severity of alopecia was graded using the Hamilton-Norwood scale. Fasting blood samples were analyzed for serum total cholesterol, triglycerides, low-density lipoprotein cholesterol (LDL-C), and high-density lipoprotein cholesterol (HDL-C). Dyslipidemia was defined according to the National Cholesterol Education Program Adult Treatment Panel III (NCEP ATP III) criteria. Data were analyzed using SPSS version 26. Results: The mean age of patients was 32.8 ± 6.4 years. Overall, 82 out of 130 patients (63.1%) had dyslipidemia. Elevated total cholesterol was observed in 39 patients (30%), high LDL-C in 44 patients (33.8%), hypertriglyceridemia in 36 patients (27.7%), and low HDL-C in 52 patients (40%). The frequency of dyslipidemia increased significantly with higher grades of alopecia (p < 0.05). Conclusion: Dyslipidemia is highly prevalent in male patients with AGA, with a strong association between severity of alopecia and lipid abnormalities. Early screening of lipid profiles in these patients is recommended to identify at-risk individuals for cardiovascular disease. Keywords: Androgenetic alopecia, Dyslipidemia, Male-pattern baldness, Lipid profile, Cardiovascular risk